BMS423: Microbial Processes / Faculty of Applied Sciences - UiTM, Faculty of Applied Sciences (2016)
A comprehensive course dealing with microbial products derived from current industrial fermentation processes. It also includes bioresource utilization, energy from renewable resources, bioreactor types and design.